Enrolment trends in a comprehensive HIV programme in rural north-central Nigeria: improved care indices, but declining quality of clinical data over time. (30th March 2015) - Aliyu, Muktar H.; Blevins, Meridith; Arinze, Folasade; Megazzini, Karen M.; Bussell, Scottie; Dunlap, Julie; Odoh, Chisom; Gebi, Usman I.; Muhammad, Mukhtar Y.; Shepherd, Bryan E.; Audet, Carolyn M.; Vermund, Sten H.; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Vanderbilt University affiliate Friends in Global Health was funded in 2008 to support comprehensive HIV/AIDS services in north-central Nigeria. We summarise programme characteristics and trends in enrolment and quality of data collection in this rural, resource-limited environment. Methods: We used routinely collected programme data in supported sites from June 1 2009 to September 30, 2013.Baseline characteristics were defined as those collected closest to a 90-day window period before and after enrolment. Summary characteristics were compared by site and enrolment year. Results: We enrolled 3, 960 HIV-infected patients into care (68% women), median age of 32 years [interquartile range (IQR): 27–40]. Most clients were married (79%) and unemployed (60%). At enrolment, median CD4+ cell count was 230 cells/μL (IQR: 114–390) and haemoglobin was 10.7 g/dL (IQR: 9.3–11.9). Advanced clinical disease [World Health Organization (WHO) clinical stage III/IV] at enrolment was documented in 29% of clients. Cumulative enrolment increased from 377 patients in 2009 to 3, 960 patients by 2013.With each successive year, more clients were enrolled at earlier stages of disease; in 2009, 37% of patients were identified as WHO clinical stage I, while in 2013, 55% of patients were so classified. While documentation of clinical staging remained stable, the completeness of CD4+ cell count and haemoglobin data declined with time. Conclusion: Expanded testing in a comprehensive HIV programme in rural Nigeria brought persons to care at earlier stages of illness. Yet, as clinical services expanded, data collection quality declined. The paradox of successful scaling up HIV services but deteriorating quality of data underscores the importance of data management training and quality improvement efforts.